PEMBUATAN ARANG AKTIF KAYU KARET UNTUK NAHAN PEMURNI MINYAK DAUN CENGKEH - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1991)
EzperlmentaUtudy   on ltmna •activation    of rubber  wood  charcoal (Hewa  bnalllMn•)   to prodw    activated claarooal.•  reported in tlu. paper.  The PurPo•   of tlu. ,...,.ch    la to dudy   the           of tempeniture and reaction time on the activa te<I charcoal yield  and quality.    .                                                                                                                                                                                                                                                                                                                                                                                                             De  octlvated eharcoal jlroduced from flail uperiment N   utm.ed to re'/lnllthe crude oa from elo•   ,_,  oa.  TflS   fr*ltmlmt    tem,,.,ature  for actlva"tion were  at  two leriela,  1000~  and BOOOC, roith  ru~         N8etlon  ti,_.   Of 10, 16 and JO minuta.  Steam /fbw rate wa  made ca...tant at 0.64 "'""•                                                     7'fN rault   Mou.   that  the yield  of  activated Charcoal range from  73.7 •to  90.0CJa,  moiature contont •from  3.9 to 9.0CJa, ah  content '/t'Om 8.9 to 4. 7CJa, volatile matter 'from 6.6 to i 3.0CJa, f&ed carbon from 83.0 to 89.8"                • Tfae  aaorptive oapa~•   o,. iodi•,    benune  and nl(uric  acid re.,,.Ctive1y rarwed from 48_6.9 to 197.1 mf/1,   11.8 to 18.4'11 and  19.6  tO U.6'1.  •ne_ food  quality of  the activated charcoal  produced when the activation temperature of 100oC ullth readlon•tl,,,. fpr 16 mlnuhtor when the mnperature  8000C withreactlOn time 10 minut•    ftfl   ilapecltilly true '(or the• ad«Jrptlve   oapadty   of  iOdine  where  thia criterion ha   Nt   the commerdal .mndard• requirement   both by the American Water Worlu A.llociotion and the lndonemn Indutrial Standard.fte    quality of  the clove  'leaf oil re'fined•with the uperimentol actiuated charcoal  ahorn  that the total e1111enol content ra•ed   .from  78.J to 79.0'11; apecific iravity   'from 1.0296 to 1.0310; nDJO from 1.6294 to 1.6J97; 80lubility  in ethanol 70'11 from 1:1 to l :.J.7'le p    chrornatofraphy   analyae• indicated .that  the e1111enol content ra1J6ed 'from 69.6 to 71.0'11andthe tnpen  content 'frorn J7.J  to 28.BWa. -De  quality of the refined  clove  'leafoil ha   been. inproved to con(Orm •Ith  the •commerdal quality• acoortlbw to the Indonaian Industrial Standard.